2021
DOI: 10.3389/fnut.2021.751992
|View full text |Cite
|
Sign up to set email alerts
|

Cereus sinensis Polysaccharide Alleviates Antibiotic-Associated Diarrhea Based on Modulating the Gut Microbiota in C57BL/6 Mice

Abstract: The present study investigated whether the purified polysaccharide from Cereus sinensis (CSP-1) had beneficial effects on mice with antibiotic-associated diarrhea (AAD). The effects of CSP-1 on gut microbiota were evaluated by 16S rRNA high-throughput sequencing. Results showed that CSP-1 increased the diversity and richness of gut microbiota. CSP-1 enriched Phasecolarctobacterium, Bifidobacterium and reduced the abundance of Parabacteroides, Sutterella, Coprobacillus to near normal levels, modifying the gut m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Because the intestinal flora is considered to be an organ that helps to regulate the metabolism of the host, the change of intestinal flora leads to the change of metabolic pathway, and the most obvious one is that the amino acid metabolism will obviously increase in AAD mice ( 34 ). Moreover, amino acid can enhance cell metabolism, increase the synthesis of protein by regulating protein translation, and increase the content of mitochondria in skeletal muscle and adipocytes, which is essential to maintain normal physiological internal environment balance ( 56 ). Carbohydrate metabolism can regulate cellular processes and provide material basis for other metabolic pathways ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…Because the intestinal flora is considered to be an organ that helps to regulate the metabolism of the host, the change of intestinal flora leads to the change of metabolic pathway, and the most obvious one is that the amino acid metabolism will obviously increase in AAD mice ( 34 ). Moreover, amino acid can enhance cell metabolism, increase the synthesis of protein by regulating protein translation, and increase the content of mitochondria in skeletal muscle and adipocytes, which is essential to maintain normal physiological internal environment balance ( 56 ). Carbohydrate metabolism can regulate cellular processes and provide material basis for other metabolic pathways ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…RAW246.7 macrophages were added to 96-well culture plate at a concentration of 1 × 10 5 cells/mL (200 μL/ well). All cells were divided into 8 groups (n = 6) and cultured for 12 h. The eight groups were blank group, control group (final concentration of 2 μg/mL LPS) and six treatment groups with LCFP-3 (1,5,25,100,200 and 300 μg/mL), respectively, in the absence of LPS (final concentration of 2 μg/mL). RAW 246.7 macrophages in the experimental groups were precultured for 1 h with LCFP-3 and then LPS was added.…”
Section: Nuclear Magnetic Resonance Spectrummentioning
confidence: 99%
“…The inflammatory reaction involves complex mechanisms accompanied by the production of pro‐inflammatory cytokines and inflammatory mediators such as tumor necrosis factor, nitric oxide (NO). Inflammation is closely related to the pathogenesis of chronic diseases such as antibiotic associated diarrhea, inflammatory bowel disease, cancer [1–3] . Macrophages are related immune cells that play important roles in the process of inflammation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive studies have indicated that polysaccharides, as prebiotics, can promote the growth of beneficial bacteria and regulate the levels of metabolites of gut microbiota, for which the host physiology, particularly gastrointestinal health, can be improved. Previous studies have shown that several herbal polysaccharides can alleviate AAD based on modulating the gut microbiota [ 6 , 16 , 17 , 18 , 19 ], but the efficacy and mechanism of PCP in the treatment of AAD remain to be explored in more depth.…”
Section: Introductionmentioning
confidence: 99%